Development of a Web-Based Rolling and Attendance System for News Coverage Employees at the Communication and Information Office (Kominfo) of Bima City - Nabila Melani Putri; Fathir; Suci Faaza Naafia; Muhammad Amirul Mu'min (Indonesian Applied Research Computing and Informatics, 2025)
The management of attendance and assignment of news coverage tasks at the Public Relations Division of Kominfo Bima City has previously been handled manually, resulting in inefficiency and disorganization. This study aims to develop a web-based system that facilitates digital employee attendance recording and automated rolling of news coverage assignments. The development method used is the Waterfall model, involving stages of requirement analysis, system design, implementation, and testing. The system is developed using PHP as the programming language and MySQL as the database, with a responsive user interface built using HTML and CSS. Implementation results show that the system can record real-time attendance, distribute assignments fairly, and ease the performance monitoring of employees. This system is expected to improve work efficiency and support digital transformation in government institutions, especially in public relations workforce management.